Caracterização, imobilização e aplicação das lipases de candida rugosa e geotrichum candidum produzidas em meio contendo melaço de soja - Morais Júnior, Wilson Galvão de (2017)
Lipases are enzymes that hydrolyses the esters in glycerol, often used for biotechnological and industrial applications. Candida rugosa and Geotrichum candidum lipases are known to have characteristics such as broad substrate specificity, tolerance toward organic solvents and high thermal stability. Thus, the present work has the general objective to characterize, immobilize and apply the of lipase from C. rugosa and G. candidum produced in a culture medium composed of soybean molasses. The molecular weight determined by SDS-PAGE was 59.7 kDa for the C. rugosa lipase, and 38.3 kDa for the G. candidum lipase. The soluble lipase from both microorganisms show maximum enzymatic activity at a temperature of 40 °C and were inhibited at pH 10. The C. rugosa lipase Km was 200.53 μM and Vmax 0.044 μmol/min, the G. candidum lipase showed a Km and Vmax of 443.99 μM and 0.382 μmol/min, respectively. Both lipases suffer inhibition only in the presence of the metal ion Cu3+. The immobilization of these enzymes was performed by adsorption on Octyl-Sepharose, by covalent unipontual bond on Cyanogen bromide (CNBr), by ionic bond on Diethylaminoethyl (DEAE) ionic bond, Monoaminoethyl–N–Ethyl (MANAE), carboxymethyl and sulfopropyl, and by multipoint covalent attachment on heterogeneous support aminoglyoxyl (AMG). The derivatives immobilized were characterized in relation to pH, thermal stability and organic solvents effect. The lipases studied had their stability improved when compared to soluble enzyme. At 50 °C, the G. candidum lipase immobilized on AMG retained the activity at 90% for 7 hours, and C. rugosa lipase immobilized on CNBr was more stable reducing the residual activity in 25.76 % in 7 hours. The lipases studied immobilized on AMG had improved stability resulting in a residual activity higher than 95%, at pH 10. Compared to soluble enzymes, the derivatives immobilized on cationic supports carboxymethyl and sulfopropyl (more stable) were up to 6-fold more stable in the presence of methanol, up to 11-fold more stable in the presence of methanol and up to 10-fold more stable in the presence of cyclohexane. The immobilized derivatives were applied in hydrolysis of sardine oil for the production of polyunsaturated acids (PUFA) Omega-3. The lipase of C. rugosa (soluble and immobilized derivatives) showed higher selectivity (EPA/DHA) compared to the selectivity produzidade by G. candidum lipase. The derivatives immobilized on carboxymethyl and sulfopropyl were those with greater selectivity, 11 for C. rugosa lipase and 7 for G. candidum lipase. When applied in enantioselective hydrolysis of (R,S) - mandelic acid ethyl ester, the C. rugosa lipase immobilized on AMG showed higher selectivity for the S isomer at pH 5 and 7, already at pH 9 to increased selectivity was the isomer R. G. candidum lipase immobilized on CNBr and AMG, has greater selectivity for the S isomer at acid and alkaline pH, and at neutral pH is greater selectivity for isomer R. This enzyme immobilized on carboxymethyl has the opposite behavior when compared between the cationic and anionic supports. When immobilized on DEAE, G. candidum lipase is more selective for the isomer R at pH 5 and 7, and at pH 9 its selectivity is greater to isomer S. The opposite happens when immobilized on carboxymethyl. The immobilization techniques, as well as the support used, is an efficient method for enzymes, such as lipases which undergo dramatic changes in its conformation during catalysis, and may change the catalytic properties improving its stability with pH, thermal and in presence of organic solvents.